KEPUASAN SUBSCRIBER DALAM MENONTON CHANNEL VIRTUAL YOUTUBER “CECILIA LIEBERIA” - Danang Herzidan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The emergence of Virtual YouTubers as a form of digital entertainment has created new patterns of interaction between content creators and audiences, making subscriber satisfaction an important aspect to investigate. From the Uses and Gratifications perspective, audience satisfaction is examined by comparing Gratification Sought (GS), representing expected gratification, with Gratification Obtained (GO), representing the gratification received after media consumption. This study aims to analyze subscriber satisfaction in watching the Cecilia Lieberia Virtual YouTuber channel based on the comparison between GS and GO. A quantitative approach with a comparative method was employed involving 100 subscribers selected through simple random sampling. Data were collected using a Likert-scale questionnaire based on McQuail's four Uses and Gratifications Indicators: information, personal identity, social interaction, and entertainment. The findings indicate that GO exceeded GS in the information, personal identity, and social interaction Indicators, while both scores were identical in the entertainment Indicator. The largest positive gratification discrepancy was found in the social interaction Indicator (+0.12), whereas the entertainment Indicator demonstrated a balance between expected and obtained gratification. These findings indicate that the Cecilia Lieberia Virtual YouTuber channel fulfilled subscriber needs across all four Indicators and support the relevance of the GS–GO model for evaluating audience satisfaction in digital media.